A review on the mechanical properties of synthetic and natural fiber-reinforced polymer composites and their application in the transportation industry - Bazli , Leila; Bazli, Milad (Journal of Composites and Compounds, 2021)
The application of fiber-reinforced polymer (FRP) composites has achieved significant attention in the industry of transportation, specifically as metal substitutes due to a need for fabricating stable and fuel-efficient airplanes, vehicles, and ships. Excellent strength, resistance to corrosion, lightweight, and suitable fatigue endurance are some of the desirable properties that would encourage the use of FRP composites in the transportation sector. Polymer-based composite materials, combining the favorable properties of both polymer matrix and reinforcing fibers, can contribute to several excellent behaviors of the obtained material. Epoxy, polyethylene, and polypropylene are the primary polymer matrices used in FRP composites. The main reinforcing fibers incorporated in fiber-reinforced composites are made out of glass, carbon, basalt, hemp, or natural resources (e.g., sisal and jute). Due to high cost, low Young's modulus, low durability, and linear stress?strain behavior to failure of the FRP materials, which are used in transportation infrastructure, the objective of this review article is to study the recent aspect of reinforced polymers with a close focus on their mechanical properties in order to evaluate their application in maritime, automotive, and aerospace.